Small interfering RNA targeting NF-κB attenuates lipopolysaccharide-induced acute lung injury in rats. Issue 1 (December 2016) - Li, Ning; Song, Yuanbin; Zhao, Wei; Han, Tingting; Lin, Shuhui; Ramirez, Oscar; Liang, Li
Abstract Background To investigate the anti-inflammatory effects of specific small interfering RNA targeting NF-κB on lipopolysaccharide (LPS)-induced acute lung injury (ALI) in rats. Method Acute lung injury was induced in Sprague-Dawley rats by intraperitoneal injection with LPS (5 mg/kg), followed by immediate intratracheal instillation of siRNA targeting NF-κB p65 (40 μg/ml). Animals in each group were sacrificed at 1 h or 8 h after the instillation. Pulmonary histological changes were evaluated by hematoxylin-eosin staining. The levels of NF-κB and TNF-α were measured by qRT-PCR. Expressions of NF-κB in lung cells and TNF-α in bronchoalveolar lavage fluid (BALF) were determined by western blot analysis and enzyme-linked immunosorbent assay (ELISA) respectively. Results LPS administration reduced the rectal temperature and white blood cell counts at 1 h, increased lung wet/dry weight ratios, caused evident lung histopathological injury, and increased the detectable transcript and cytokine levels of TNF-α in lung tissue in BALF. siRNA targeting of NF-κB p65 effectively abrogated the expression of NF-κB p65 in lung cells and, aside from rectal temperatures, ameliorated all changes induced by LPS. Conclusions NF-κB knockdown exerts anti-inflammatory effects on LPS-induced ALI especially in the initial phase, which may be due in part to reduced levels of the proinflammatory cytokine TNF-α. NF-κB siRNA's rapidity and effectiveness to abrogate ALI development may provide an effective therapeutic method with future clinical applications.